Pengaruh Kebijakan Pendidikan terhadap Sektor Kesehatan dan Ekonomi: Tinjauan Literatur Multisektoral - Loso Judijanto; Rosdiana Rosdiana; Mistari Ulfa (Jurnal Ilmiah Edukatif, 2025)
The influence of education policy on the health and economic sectors is very important and interrelated, as reviewed in this multisectoral literature. This study concludes that effective education policy can improve the quality of life by supporting individual health and strengthening the economy. In the health sector, adequate education increases awareness and preventive action, thus reducing disease rates and increasing the use of health services. In the economic sector, quality education improves the skills and productivity of the workforce, encourages innovation, and increases people's incomes, which together stimulate economic growth. Therefore, integration and synergy between sectors is key to designing policies that bring maximum benefits to society.